Algal polysaccharides and derivatives as potential therapeutics for obesity and related metabolic diseases. Issue 22 (25th October 2022) - Yang, Zizhen; Wang, Haoyu; Liu, Nian; Zhao, Kunyi; Sheng, Yingying; Pang, Hao; Shao, Kaidi; Zhang, Mengyao; Li, Shangyong; He, Ningning
Abstract : The potential and challenges of algal polysaccharides and their derivatives as potential therapeutic agents for obesity and its related metabolic diseases. Abstract : The worldwide upward trend in obesity has been dramatic, but there is a lack of effective and safe drug treatment. Marine-derived algal polysaccharides, including fucoidan, alginate, polysaccharide of Spirulina platensis (PSP), ulvan, rhamnan sulfate (RS), laminarin, agar, and carrageenan, are widely used in combination with wound healing, drug delivery, and tissue-related biomedical research engineering. Recently, the prebiotic effects of algal polysaccharides and their related derivatives have received more and more attention. In this review, we discuss the potential and challenges of algal polysaccharides and their derivatives as potential therapeutic agents for obesity and its related metabolic diseases. Relevant studies have demonstrated that a variety of algal polysaccharides can play a significant role in weight loss and treatment of obesity-related metabolic diseases by improving the composition of gut microbiota, promoting bile acid formation, and upregulating cholesterol receptors in the liver. Because of their low price, non-toxic properties, and easy availability, algal polysaccharides have the potential to be developed as weight loss products.